2017
DOI: 10.11114/jets.v5i6.2327
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Effects in Second Language Acquisition: An Annotated Survey

Abstract: The aim of this study is to investigate the relationship between frequency and language acquisition from many perspectives including implicit and explicit instruction, frequency effects on morpheme acquisition in L2, the relationship between frequency and multi-word constructions, frequency effects on phonetics, vocabulary, gerund and infinitive constructions, bitransitive constructions, and so on. In his impressive article on frequency, Ellis (2002a) asked this crucial question about the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…And many studies found that acquisition is closely related to frequency (e.g. Ellis, 2002; Koprowski, 2005), and both corpus and experimental data show that input frequency has a significant impact on second language acquisition (Kartal & Sarigul, 2017). In word recognition, frequency is one of the strongest predictors of processing efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…And many studies found that acquisition is closely related to frequency (e.g. Ellis, 2002; Koprowski, 2005), and both corpus and experimental data show that input frequency has a significant impact on second language acquisition (Kartal & Sarigul, 2017). In word recognition, frequency is one of the strongest predictors of processing efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The present study finds that exposure frequency exerts a significant effect on IVA and that seven is the threshold value for IVA through extensive reading to occur. Kartal & Sarigul (2017) argue that input frequency significantly influences second language acquisition. This is particularly true with IVA through reading.…”
Section: A Frequency Effect On Ivamentioning
confidence: 99%
“…Frequency, and more specifically frequency in the input is defined as -the relative frequency of formal features in the language that people hear or read (Vanpatten and Benati, 2010) as cited in Kartal and Sarıgül (2017). The frequency of linguistic structures (the word -structure‖ is purposively used in this context, to refer to a grammatical on the second language acquisition process since the frequency of structures a learner is exposed to promotes the process of acquiring a second language (MacWhinney, 1997;Ellis, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%